KEBIJAKAN DIVIDEN DALAM PERSPEKTIF CATERING THEORY - Rustan, Priscilla Leony; Daromes, Fransiskus Eduardus; Lukman, Lukman; Kampo, Kunradus (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
This research is aimed to investigate the role of dividend premium and share repurchases in influencing the companies’ dividend policy. The theory used in this research is catering theory. This research uses secondary data obtained by using observation method. The data source in this research is the annual reports of manufactur companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2019. The sample were selected using purposive sampling method, with a total of 98 companies. This research uses analysis double linear regression test using SPSS version 20 software. The result of this research indicate that dividend premium has a positive and significant effect on dividend policy. Share repurchases has a negative and significant effect on dividend policy